2014
DOI: 10.1097/rli.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance–Guided High-Intensity Focused Ultrasound Treatment of Locally Advanced Pancreatic Adenocarcinoma

Abstract: Our preliminary clinical experience suggests that MRgFUS is a feasible and repeatable ablative technique in selected patients with unresectable and device-accessible pancreatic adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
(25 reference statements)
1
41
0
2
Order By: Relevance
“…Breath-holding or gating techniques can be applied to overcome the motion of abdominal organs due to breathing [18,19]. These techniques extend the treatment time due to limited duration and repetition frequency of the anaesthesia and the reduction of active FUS exposure time.…”
Section: Respiratory Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breath-holding or gating techniques can be applied to overcome the motion of abdominal organs due to breathing [18,19]. These techniques extend the treatment time due to limited duration and repetition frequency of the anaesthesia and the reduction of active FUS exposure time.…”
Section: Respiratory Motionmentioning
confidence: 99%
“…The first MR-guided liver ablation was performed by Okada et al in 2006 [18]. Recently, Anzidei et al [19,20] reported the successful treatment of selected patients with pancreatic adenocarcinoma and patients with a single liver tumour using a breath-holding technique under general anaesthesia.…”
Section: Fus In Abdominal Organsmentioning
confidence: 99%
“…Here, especially sonographic-guided HIFU applications have already been well established, whereas MR-HIFU approaches are now upcoming therapeutic advancements. 16,[55][56][57] Especially, targeted vessel ablation by MR-HIFU could mean an interesting approach in curative as well as palliative oncologic treatments. 58 MR-HIFU treatment of breast cancer is now in development as tumor necrosis of up to 100% has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31] In addition, several applications have been tested in fields other than oncology, including MSK diseases and neurology (e.g. essential tremor, neuropathic pain etc.).…”
Section: Mrgfus Lessons Learned From Non-musculoskeletal Applicationsmentioning
confidence: 99%